THE MAIN CRITERIA FOR THE DEVELOPMENT OF CONFLICT PSYCHOLOGICAL TRAINING PROGRAMS - Mamayusupova Iroda Xamidovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, a growing body of research proves the existence of positive functions of conflict is, in a certain sense, positive. Such a situation, firstly, draws the attention of society to issues that need to be addressed, and secondly, the positive resolution of conflicts serves development. For teenagers, this requires a special approach. Conflict requires new approaches to prevent and avoid situations. The emphasis now is not only on conflict resolution but also on the transition to conflict management.